Characteristics and sources of PM2.5 and reactive gases near roadways in two metropolitan areas in Canada. (1st December 2019) - Dabek-Zlotorzynska, Ewa; Celo, Valbona; Ding, Luyi; Herod, Dennis; Jeong, Cheol-Heon; Evans, Greg; Hilker, Nathan
Abstract: With concern in recent years about adverse health effects for populations living or spending significant amounts of time near large roadways, an investigation of the air quality characteristics and potential sources influencing levels of PM and its chemical composition was undertaken in Toronto and Vancouver. Three near-road monitoring stations were established in the downtown area and beside a large highway in Toronto, and beside a major trucking route in Vancouver. 24-hour integrated samples were concurrently collected at these near-road and nearby urban background sites. This study has provided detailed chemical data for PM2.5 and reactive gases (NH3, HONO and HNO3 ) for a year in 2015–2016. Differences between pollutant concentrations at the near-road and background urban sites were identified, and compared with observations at other urban locations. The traffic contribution was quantified as the concentration increment between the near-road and background sites. The highest increments due to traffic were observed for elemental carbon, select trace metals (e.g. Fe, Ba, Cu, Sb, Zn) and reactive gases (NH3, HONO). In general, the percent contribution of local traffic-related emissions followed a descending order of Toronto highway > Vancouver truck route > downtown Toronto for most of these pollutants. It appears that the influence of traffic-related emissions on air pollution near roads depends more on the proportion of large trucks in the fleet than the total traffic volume. Application of principal component analysis (PCA) coupled with multi-linear regression (MLR) analysis to the local traffic increment pollutant data, as well as knowledge of chemical markers representative of different sources, helped to identify the possible sources of traffic-related PM2.5 . These sources include non-exhaust (brake wear abrasion, resuspended road dust) and vehicular exhaust (mixed gasoline/diesel, diesel and lubricating oil combustion) emissions. The contribution of each of the sources varied between sites. In particular, the contribution of diesel exhaust emissions, presumably from highly polluting heavy-duty vehicles and trucks, was significant at the truck route (Vancouver) and the highway (Toronto) sites. Furthermore, the substantial contribution of non-exhaust emissions (brake wear and resuspension of road dust) to PM2.5, and thus metals, with differences between sites due to traffic characteristics or local meteorology was identified. Emissions related to lube oil combustion were not statistically significant. Overall, this work delivered valuable information that serves as input for further studies involving other roads and cities in order to generate reliable and representative results for air quality management and associated health outcomes. Highlights: A near-road sampling campaign was conducted in Toronto and Vancouver. Detailed chemical data for PM2.5 and reactive gases are provided. PCA/MLR was applied to the local traffic increment pollutant data. Diesel traffic was the significant contributor to air pollution. The substantial contribution of non-exhaust emission was identified.